Compare the quality of life in fertile and infertile women attending public - Direkvand-Moghadam, ashraf; Delpisheh, ali; Direkvand-Moghadam, azadeh (Advances in Nursing & Midwifery, 2015)
Background and aim: Infertile women experience many problems in their life. Evaluation the quality of life in infertile makes the healthcare provider aware of their needs for providing quality care. The aim of present study was to compare the quality of life in fertile and infertile women attending public and private centers I Ilam,Iran. Methods and material : In a cross - sectional study , quality of life of a group of infertile and fertile women attending to public and private health care centers of Ilam in 2013 was compared. Simple random sampling method was used. Inclusion criteria consisted of: being married, age between 15-49 years , nonpregnant and non-lactating. Postmenopausal women with known physical and mental illness, or a history of them were excluded. Data were collected by the quality of life questionnaires SF-36 and demographic questionnaire. Data were analyzed using SPSS software, chi-square test and t-test. Results: 450 women participated in the present study . Mean age in women of fertile group was 32.17± 3.09 years and in infertile women 35.93± 8.07, respectively. The mean scores for physical functioning, role limitations due to physical problems, general health, vitality, social functioning, role limitations due to emotional problems and mental health were significantly different in fertile and infertile women. But the physical pain scores were not significantly different in fertile and infertile women. Conclusion: The physical and mental dimensions of quality of life scores was lower in infertile women in comparison to fertile women group . Therefore it is important to provide support and education to improve quality of life in infertile women. Key words: Infertility, quality of life, SF-36